Maximizing ESP Learning with Chatbot Technology: An Evaluation of Effectiveness - Ayuningtyas, Pratika (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2024)
This study investigated how students of vocational higher education could use chatbot technology as a digital learning resource. According to the research findings, the chatbot responded students' questions instantly and provided a helpful resource for discovering specific information. The chatbot also served as a handy learning tool that was accessible anywhere and at any time, allowing for individualized and independent learning experiences. Furthermore, the interactive features of the chatbot promoted interesting discovery and interactive education, which improved student involvement in many learning contexts. Improvements are also proposed, including the development of chatbot capability for instant messaging programs, the integration of student scoring capabilities, and the expansion of topic coverage through linkages to other particular courses. A more thorough understanding would result from these improvements.